Interatomic interaction in diatomic molecules with taking into account the repulsion of ions in a positively charged core - Gretchikhin, Leonid (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: Different types of interactions in diatomic molecules of complex atoms are analysed. Methods: The empirical formulas of Lennard-Jones, Buckingham, Buckingham-Corner, Morse, Danem, Gulbert-Hirschfelder, Klein and their combinations without their clear physical justification are used to take into account the repulsive and attractive forces in the molecule. To improve the situation of the binary interaction inside condensed matter, Gretchikhin and his associates proposed applying the Heitler-London quantum theory, but only at distances greater than equilibrium. At distances less than equilibrium between atoms in the binary interaction, the Lennard-Jones formula was still used. Using various kinds of fitting coefficients, in each case we obtained a match with the experimental data on the dissociation energy. A more general idea of ​​all possible types of interactions was completely absent. In this connection, the need arose to reveal all possible types of interactions inside diatomic molecules and theoretically obtain dissociation energy, activation energy, and standard atomization enthalpy. The application of quantum mechanics methods in the Heitler-London theory allowed to take into account not only the Coulomb deterrence during exchange interaction, but also the Coulomb repulsion of nuclei. Results: The electric dipoles for neutral atoms and for positively charged ions of the core of diatomic molecules were calculated. This made it possible to calculate the electron-dipole and dipole-dipole interactions. A theory of the repulsion of positively charged nuclei of complex atoms in diatomic molecules has been developed. The interaction potentials for the molecules of carbon, nitrogen, oxygen, aluminum, silicon, and sodium are calculated. The developed physical model of the formation of diatomic molecules is compared with the empirical potentials of Lennard-Jones and Morse. At the internuclear distance equal to the sum of the energy radii of atoms in the molecule, a potential jump occurs with a transition from the negative to the positive region of binding energies, which determines the activation energy of the formation of diatomic molecules. Conclusion: From the obtained interaction potentials of atoms in diatomic molecules, the activation energy, ionization energy, standard atomization enthalpy, and electron affinity are determined.